SOSIALISASI KESEHATAN DAN ASI EKSKLUSIF BAGI IBU DI WILAYAH KERJA UPTD PUSKESMAS KEBUN SIKOLOS KECAMATAN PADANG PANJANG BARAT KOTA PADANG PANJANG - Syafrawati Syafrawati; Annisa Afritika; Nadya Vebrielna (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
Exclusive breastfeeding is given to infants from 0-6 months without additional food. Data from Padang Panjang City Health Office shows that the coverage of exclusive breastfeeding in 2012 was 45%. This amount is not in accordance with RPJMD target (2010-2014) of 65%. Sikolos Garden Health Center is located in West Padang Panjang. One of problems with the Nutrition and MCH program is the low achievement of exclusive breastfeeding, which is 14.9%. There are factors that become obstacles in increasing the achievement of exclusive breastfeeding, such as the lack of knowledge and public awareness about the benefits of exclusive breastfeeding, there are mothers who think that exclusive breastfeeding will change the shape of breast, and socio-cultural factors that say babies do not full if only consume breast milk. Therefore, it is necessary to make efforts to increase the achievement of exclusive breastfeeding coverage in the Working Area of Kebun Sikolos Health Center. The purpose of this activity is to increase mother's knowledge about the importance of exclusive breastfeeding for babies so that they can increase the achievement of exclusive breastfeeding coverage in the Work Area of the Kebun Sikolos Health Center. The activity was carried out using health promotion methods in the form of counseling about exclusive breastfeeding, as well as making health promotion media in the form of posters, leaflets, and lactation corners. After counseling, there was a significant increase in the knowledge of pregnant women and breastfeeding mothers about exclusive breastfeeding. Based on the results of pre-test (60%) and post-test (100%). It is suggested the need for increased counseling in Mother's class forums about exclusive breastfeeding, breast care during pregnancy, and adequate nutrition for breastfeeding mothers so that breast milk production is met